Effective Combination Therapy with Nizatidine and Acotiamide for Functional Dyspepsia - Kajihara, Yusaku (The Indonesian Society for Digestive Endoscopy, 2025)
Background: The two subgroups of Functional Dyspepsia (FD), including Postprandial Distress Syndrome (PDS) and Epigastric Pain Syndrome (EPS), can overlap. PDS–EPS overlap tends to reduce patients’ quality of life. Combination therapy with nizatidine and acotiamide may improve the symptoms of FD, including PDS–EPS overlap. A previous study reported the combined effect of rabeprazole and acotiamide. This study aimed to evaluate nizatidine as an alternative to rabeprazole.Methods: This single-center retrospective study analyzed 66 patients with FD, including 45 and 21 patients receiving nizatidine/acotiamide and rabeprazole/acotiamide therapies, respectively. The regimen comprised nizatidine 150 mg twice daily, rabeprazole 10 mg once daily, and acotiamide 100 mg thrice daily. No prokinetics other than acotiamide (e.g., rikkunshito and mosapride) were simultaneously administered. The following characteristics were investigated: age, sex, diabetes mellitus, Parkinson’s disease, mental illness, subgroups of FD (PDS, EPS, or PDS–EPS overlap), and treatment-emergent adverse events. Symptom improvement rates following treatment were calculated and compared.Results: Although differences in the FD subgroups were significant in terms of patients’ backgrounds, no significant difference in PDS–EPS overlap rates was observed (55.6% [25/45] vs. 61.9% [13/21], p = 0.79). The difference in symptom improvement rates between nizatidine/acotiamide and rabeprazole/acotiamide therapies was not significant (86.7% [39/45] vs. 85.7% [18/21], p = 1).Conclusion: Nizatidine/acotiamide therapy demonstrated efficacy comparable to rabeprazole/acotiamide therapy in treating FD. Patients with FD frequently experience treatment difficulties owing to various underlying factors; however, nizatidine/acotiamide therapy with a high symptom improvement rate is a promising therapeutic option in refractory FD.Keywords: Dyspepsia, nizatidine, rabeprazole